TINDAKAN PENCEMARAN NAMA BAIK DAN PENGHINAAN MELALUI MEDIA ELEKTRONIK - Rusman Rusman; Fauziyyah Mutmainah S (Universitas Suryakancana, 2021)
The development of technology and information has changed human lifestyles, including through technology and information facilities, humans can also access, provide information and carry out acts of defamation among human beings. As a nation that upholds human dignity and dignity, acts of defamation through technological means are included in the category of criminal acts and perpetrators of defamation have entered the legal area regulated by Law (UU) No. 19 of 2016 Amendments to Law No. 11 of 2008 concerning Information and Electronic Transactions, namely the internet as a medium for carrying out their actions. Perpetrators can be legally processed even if there is no complaint from the victim, but by referring to the Criminal Code as intended by the Law on Information and Electronic Transactions, the offense turns into a complaint offense (klacht delic) which requires the victim to make a complaint to the authorities.Keywords: Complaints, Dignity, Humiliation, Criminal, Sanctions.